2004
DOI: 10.1038/labinvest.3700198
|View full text |Cite
|
Sign up to set email alerts
|

Real-time quantitative RT-PCR identifies distinct c-RET, RET/PTC1 and RET/PTC3 expression patterns in papillary thyroid carcinoma

Abstract: RET/PTC1 and RET/PTC3 are the markers for papillary thyroid carcinoma. Their reported prevalence varies broadly. Nonrearranged c-RET has also been detected in a variable proportion of papillary carcinomas. The published data suggest that a wide range in expression levels may contribute to the different frequency of c-RET and, particularly, of RET/PTC detection. However, quantitative expression analysis has never been systematically carried out. We have analyzed by real-time RT-PCR 25 papillary carcinoma and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 40 publications
2
41
0
1
Order By: Relevance
“…However, the identification of RET/PTC in other common thyroid tumour histotypes such as oncocytic adenomas and carcinomas (Cheung et al, 2000), and even in hyperplastic thyroid nodules (Ishizaka et al, 1991;Elisei et al, 2001) and Hashimoto's thyroiditis (Rhoden et al, 2006), seems to challenge the validity of RET/PTC as a tumour marker and its specificity for PTC. Moreover, it has been recently shown that the level of RET/PTC expression in papillary carcinoma is highly variable, suggesting that the distribution of RET/PTC within one tumour may not be homogenous (Rhoden et al, 2004;Unger et al, 2004). This is also supported by recent fluorescence in situ hybridization (FISH) studies by ourselves and others (Unger et al, 2004;Ciampi and Nikiforov, 2007).…”
Section: Introductionmentioning
confidence: 74%
“…However, the identification of RET/PTC in other common thyroid tumour histotypes such as oncocytic adenomas and carcinomas (Cheung et al, 2000), and even in hyperplastic thyroid nodules (Ishizaka et al, 1991;Elisei et al, 2001) and Hashimoto's thyroiditis (Rhoden et al, 2006), seems to challenge the validity of RET/PTC as a tumour marker and its specificity for PTC. Moreover, it has been recently shown that the level of RET/PTC expression in papillary carcinoma is highly variable, suggesting that the distribution of RET/PTC within one tumour may not be homogenous (Rhoden et al, 2004;Unger et al, 2004). This is also supported by recent fluorescence in situ hybridization (FISH) studies by ourselves and others (Unger et al, 2004;Ciampi and Nikiforov, 2007).…”
Section: Introductionmentioning
confidence: 74%
“…In addition, the presence of RET/PTC rearrangements was confirmed by expression analysis of both extracellular (EC) domain and tyrosine kinase (TK) domain of RET, as previously described (31,32,33,34,35,36). Two pair of primers were designed to amplify the region encoding the EC domain (exons 6 and 7) and TK domain of RET (exons 16 and 18).…”
Section: Detection Of Ret/ptc Fusion Genes By Rt-pcrmentioning
confidence: 99%
“…To confirm the expression of RET fusion transcripts, we additionally evaluated the expression of both the TK and EC domains of RET was performed, as described (31,32,33,34,35,36).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Rearrangements of RET/PTC1 and RET/PTC3 were analysed by the real-time PCR using a specific TaqMan probe and reaction conditions as described previously (Rhoden et al, 2004). The reaction mixtures contained 5 ml cDNA, 12.5 ml 2 Â TaqMan PCR Master Mix and 200 nM primers plus 100 nM of probe in a final volume of 25 ml.…”
Section: Quantitative (Real-time) Rt -Pcr Analysismentioning
confidence: 99%